2022
DOI: 10.1111/jvim.16422
|View full text |Cite
|
Sign up to set email alerts
|

Antiparasitic treatment with itraconazole and amiodarone in 2 dogs with severe, symptomatic Chagas cardiomyopathy

Abstract: Chagas cardiomyopathy, caused by the protozoal parasite Trypanosoma cruzi, is characterized by arrhythmias, myocardial damage, heart failure, and sudden death. We describe 2 dogs with severe, symptomatic Chagas cardiomyopathy characterized by myocardial dysfunction and electrocardiographic abnormalities that were managed with a combination of cardiac medications and antiparasitic treatment with itraconazole and amiodarone. Both dogs died suddenly within 6 months of diagnosis. These cases highlight the need for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…In the Tc /BNZ and Tc/ UNT groups, the abnormalities were poorly differentiated bundle branch block with intraventricular conduction defect. All findings are consistent with what has been reported in dogs with CD [ 4 , 6 , 42 , 60 , 61 , 62 ]. There is a possibility that NTZ may have caused cardiotoxicity, as reported by Gong et al, who observed that exposure to the drug affected the embryonic heart development of zebrafish, significantly inhibited cardiomyocyte proliferation, and promoted apoptosis, ultimately leading to cardiac tissue injury [ 63 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the Tc /BNZ and Tc/ UNT groups, the abnormalities were poorly differentiated bundle branch block with intraventricular conduction defect. All findings are consistent with what has been reported in dogs with CD [ 4 , 6 , 42 , 60 , 61 , 62 ]. There is a possibility that NTZ may have caused cardiotoxicity, as reported by Gong et al, who observed that exposure to the drug affected the embryonic heart development of zebrafish, significantly inhibited cardiomyocyte proliferation, and promoted apoptosis, ultimately leading to cardiac tissue injury [ 63 ].…”
Section: Discussionsupporting
confidence: 93%
“…Dogs are natural hosts of T. cruzi and have been traditionally considered adequate models of Chagas disease, with an electrocardiographic and myocardial pathology that reflects human disease. 109,[131][132][133] In particular, dogs can develop a form of the disease that resembles the chronic phase of Chagas disease more closely, with changes in response outcomes following treatment with benznidazole in these animals also matching those observed in human clinical trials. 109,133,134 Nonetheless, differences in the half-life of certain drugs in dogs and humans can limit the translational potential of results obtained in this species.…”
Section: Canine Modelsmentioning
confidence: 87%
“…Echo derived RV S’ correlates with reduced RV ejection fraction in infected humans, and RV systolic dysfunction is associated with worse prognosis [ 56 ]. In dogs, RV enlargement has been associated with a worse prognosis and can be an indicator of end-stage disease [ 25 , 57 ]. Advanced echocardiographic imaging with regional speckle tracking of both ventricles may provide earlier detection of wall-motion changes and myocardial damage [ 56 , 58 ].…”
Section: Discussionmentioning
confidence: 99%